Development of a STEM-Based E-Module Assisted by Kvisoft Flipbook Maker Through the PBL Model on Energy Transformation Material to Improve Critical Thinking of Fourth Grade Students at UPT SDN Nglegok 2, Blitar Regency - Ekowati, Amanda; Mohamad fatih; Ragil Tri Oktaviani (Global Action and Education for Society, 2026)
This study aims to develop and validate a STEM-based E-Module utilizing Kvisoft Flipbook Maker integrated with the Problem-Based Learning (PBL) model, focusing on the topic of energy transformation to enhance critical thinking skills among fourth-grade students at UPT SDN Nglegok 2, Blitar. The research employed Borg and Gall’s development model consisting of seven stages: identification of potential and problems, data collection, product design, expert validation, design revision, product trial, and final revision. Validation from experts in content, media, and language indicated that the E-Module is valid and appropriate for classroom use. The module's practicality and effectiveness were tested through quasi-experimental research involving experimental and control groups. The experimental group using the developed E-Module showed a moderate improvement in critical thinking skills based on N-Gain analysis. Statistical tests, including independent sample t-test and ANOVA, confirmed significant differences and interactions between groups, demonstrating the E Module's effectiveness in promoting critical thinking. The findings suggest that the developed EModule is a valuable and feasible instructional media to enrich learning experiences in science-social studies integrated curriculum (IPAS). It supports teachers in delivering content more interactively and encourages students to engage in higher-order thinking processes.